High-flow nasal oxygen does not increase the volume of gastric secretions during spontaneous ventilation. (July 2020) - McLellan, Elizabeth; Lam, Karen; Behringer, Elizabeth; Chan, Vincent; Bozak, Didem; Mitsakakis, Nicholas; Perlas, Anahi
Abstract: Background: High-flow, heated, and humidified nasal oxygen therapy (HFNO) is frequently used in critical care and perioperative settings for a range of clinical applications. Much of the benefit of HFNO is attributed to generation of modest levels of positive airway pressure. Concern has been raised that this positive airway pressure may cause gastric insufflation, potentially increasing the risk of regurgitation and aspiration in an unprotected airway. Methods: A prospective, interventional, assessor-blinded study was undertaken to evaluate the effects of HFNO on gastric content and gastric distension in healthy fasted adult volunteers assessed by ultrasonography. The primary outcome was the volume of gastric secretions. The secondary outcomes were the incidence of gastric air insufflation and the distribution of gastric antral grades. Results: Sixty subjects were enrolled. No subject was found to have air gastric distension either at baseline or after treatment with HFNO. All subjects had either a Grade 0 or Grade 1 antrum, with similar distribution of antral grades and similar volume of gastric secretions before and after treatment with HFNO. Conclusions: There was no evidence that treatment with HFNO at flow rates of up to 70 L min −1 for 30 min resulted in gastric distension or an increase in gastric secretions in healthy individuals breathing spontaneously. The generalisability of these findings to subjects under anaesthesia and patients with incompetence of the lower oesophageal sphincter or impaired gastric emptying requires further investigation. Clinical trial registration: NCT03134937.